The universal basic income grant (UBIG): A comparative review of the characteristics and impact - Brian Mathebula (Hochschule Bonn-Rhein-Sieg, Fachbereich Sozialpolitik und Soziale Sicherung, 2021)
In recent years, public debates, pilot projects and academic research have internationally boosted the prominence of the universal basic income grant (UBIG) as a policy option. Despite this prominence, the arguments and evidence of the UBIG discussion have not been systematically put forward and discussed in light of the different UBIG conceptual understandings and applications. This paper adds value to the debate by systematic presenting the social, economical and political arguments in support of and against a UBIG. It furthermore discusses the UBIG dimensions/characteristics and variations, and also pose questions about whether all the UBIG experiments can really be classified as a UBIG. Antagonist of a UBIG often raise concerns about the negative effect of the lack of conditions and targeting in a UBIG. Since evidence on the impact of UBIG is limited, this paper turns to the evidence base on unconditional cash transfers and conditional cash transfers. The results show that it is the cash transfer rather than the conditionality and targeting that produce positive outcomes in areas of personal wellbeing.
urn:nbn:de:hbz:1044-opus-53455
Keywords: 360; Unconditional basic income grant (UBIG); cash transfers (CT); conditional cash transfer (CCT); conditionality and targeting; unconditional cash transfers (UCT)